2012
DOI: 10.1073/pnas.1202465109
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs/TP53 feedback circuitry in glioblastoma multiforme

Abstract: MicroRNAs (miRNAs) are increasingly implicated in regulating cancer initiation and progression. In this study, two miRNAs, miR-25 and -32, are identified as p53-repressed miRNAs by p53-dependent negative regulation of their transcriptional regulators, E2F1 and MYC. However, miR-25 and -32 result in p53 accumulation by directly targeting Mdm2 and TSC1, which are negative regulators of p53 and the mTOR (mammalian target of rapamycin) pathway, respectively, leading to inhibition of cellular proliferation through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 40 publications
2
112
0
1
Order By: Relevance
“…We previously showed that E2F1 enhanced Ad-p53-mediated apoptosis through p14ARF-dependent MDM2 downregulation (39) and that OBP-702 infection showed E1A-dependent MDM2 downregulation in association with apoptosis (26). Recently, E2F1 has been shown to suppress MDM2 expression by suppressing the promoter activity (40) or by inducing upregulation of miR-25/32, which targets MDM2 (41). Furthermore, E2F1-inducible miR-93/106b enhanced Ad-p53-induced apoptosis and autophagy via p21 suppression (Figs.…”
Section: Mol Cancer Ther; 12(3) March 2013mentioning
confidence: 99%
“…We previously showed that E2F1 enhanced Ad-p53-mediated apoptosis through p14ARF-dependent MDM2 downregulation (39) and that OBP-702 infection showed E1A-dependent MDM2 downregulation in association with apoptosis (26). Recently, E2F1 has been shown to suppress MDM2 expression by suppressing the promoter activity (40) or by inducing upregulation of miR-25/32, which targets MDM2 (41). Furthermore, E2F1-inducible miR-93/106b enhanced Ad-p53-induced apoptosis and autophagy via p21 suppression (Figs.…”
Section: Mol Cancer Ther; 12(3) March 2013mentioning
confidence: 99%
“…MiR-25 and miR-32 induce accumulation of p53 and subsequently inhibition of glioblastoma cell growth [124]. MiR-7 has been found to target YY1, a p53 suppressor.…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“…[21][22][23][24][25][26] Another report indicated miR-23b promoters were responsive to p53. 27 Therefore, we explored whether miR-23b expression in DN is controlled by known transcription factors, such as p53.…”
mentioning
confidence: 99%